1995
DOI: 10.1002/star.19950470303
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Changes in Cassava Starch and Flour Associated With Fermentation: Effect on Textural Properties

Abstract: Physicochochemical changes in cassava starch and flour associated with fermentation were investigated and related to textural properties of its flour pastes. Cyanide and pH decreased, while crude protein, acidity, and apparent amylose content increased in the fermented products. Average starch granule diameter, solubility, and swelling power were depressed, while gelatinization enthalpy increased. Amylograph of starch showed increased peak visocity temperature, reduced peak, breakdown, and setback viscosities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
47
2
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 17 publications
15
47
2
4
Order By: Relevance
“…This indicates that, the longer the fermentation period, the higher the microbial population and, hence, the higher the consumption of soluble sugars. This is in agreement with earlier studies [24][25][26].…”
Section: Functional Propertiessupporting
confidence: 94%
See 2 more Smart Citations
“…This indicates that, the longer the fermentation period, the higher the microbial population and, hence, the higher the consumption of soluble sugars. This is in agreement with earlier studies [24][25][26].…”
Section: Functional Propertiessupporting
confidence: 94%
“…The amylose content of the fermented flours was higher than the unfermented flour (14.79%). This observation could be explained by the likely formation of amylose-like materials resulting from enzyme/acid hydrolysis of amylopectin at the amorphous regions of the starch granule during fermentation [26]. The amylose content of the fermented cocoyam flour in this study, was close to the amylose content of fermented cassava starches (18.23-20.35%) reported by Numfor [26].…”
Section: Functional Propertiessupporting
confidence: 81%
See 1 more Smart Citation
“…The presence of these cyanogenic glucosides necessitates the processing of roots prior to consumption. Fermentation not only enhances detoxification but may also improve the quality of the food under process [7]. Traditionally, fermented cassava flour is made by soaking cassava roots in water for 3 to 5 days, followed by the process of draining, drying and milling.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, fermented cassava flour is made by soaking cassava roots in water for 3 to 5 days, followed by the process of draining, drying and milling. [7] (Numfor et al, 1995) showed that changes in physicochemical properties of cassava flour produced were attributable to the spontaneous fermentation occurring during soaking. In order to reduce the time of root softening during the fermentation process, starters can be added to the fermentation medium at the beginning of the fermentation, which can modify physicochemical properties of cassava flour.…”
Section: Introductionmentioning
confidence: 99%